Complete cloning of the Duchenne muscular dystrophy (DMD) cDNA and preliminary genomic organization of the DMD gene in normal and affected individuals. - Koenig, M; Hoffman, E; Bertelson, C; Monaco, A; Feener, C; Kunkel, L (1987)
The 14 kb human Duchenne muscular dystrophy (DMD) cDNA corresponding to a complete representation of the fetal skeletal muscle transcript has been cloned. The DMD transcript is formed by at least 60 exons which have been mapped relative to various reference points within Xp21. The first half of the DMD transcript is formed by a minimum of 33 exons spanning nearly 1000 kb, and the remaining portion has at least 27 exons that may spread over a similar distance. The DNA isolated from 104 DMD boys was tested with the cDNA for detection of deletions and 53 patients exhibit deletion mutations. The majority of deletions are concentrated in a single genomic segment corresponding to only 2 kb of the transcript.